2001
DOI: 10.1002/1097-0215(20010601)92:5<697::aid-ijc1245>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

NK cells are essential for effective BCG immunotherapy

Abstract: Adjuvant intravesical bacillus Calmette‐Guérin (BCG) therapy is a well‐established and successful adjuvant immunotherapy in the treatment of superficial bladder cancer. Although the function of natural killer (NK) cells in other immunotherapeutic regimens (e.g., lymphokine‐activated killer [LAK] cell or interleukin‐2 [IL‐2] therapy) has been established, the contribution of NK cells to effective BCG immunotherapy is not clear. We used a human in vitro system to analyze the role of NK cells in BCG‐induced cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
134
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(140 citation statements)
references
References 25 publications
1
134
0
5
Order By: Relevance
“…Furthermore, Il-6 seems to contribute to MHC-nonrestricted cytotoxic activity by inducing natural killer (NK) cell proliferation. Nowadays, NK cells are considered as essential, cytotoxic effector cells during BCG therapy ( Figure 1H) (Brandau et al, 2001).…”
Section: Secretion Of Cytokines By Urothelial Tumour Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Il-6 seems to contribute to MHC-nonrestricted cytotoxic activity by inducing natural killer (NK) cell proliferation. Nowadays, NK cells are considered as essential, cytotoxic effector cells during BCG therapy ( Figure 1H) (Brandau et al, 2001).…”
Section: Secretion Of Cytokines By Urothelial Tumour Cellsmentioning
confidence: 99%
“…A key role is supposed for NK cells (Brandau et al, 2001). NK cells, a special population of mononuclear cells, recognise 'self'-peptides presented by MHC class I molecules on the surface of cells.…”
Section: Secretion Of Cytokines By Urothelial Tumour Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective BCG therapy requires induction of a T-cell-mediated immune response (Ratliff et al, 1987;Ratliff, 1992) and the activation of a natural killer (NK) cell-like population with an apparent ability to distinguish between normal and cancer cells (Bohle et al, 1993;Brandau et al, 2001). Significantly, both T-celland NK-cell-deficient mice respond poorly to BCG therapy (Brandau et al, 2001).…”
mentioning
confidence: 99%
“…Significantly, both T-celland NK-cell-deficient mice respond poorly to BCG therapy (Brandau et al, 2001). Following BCG instillation, it has been shown that there is an accumulation of immunocompetent cells into the bladder wall including activated T helper (Th) lymphocytes, NK cells and DCs; adhesion molecules (ICAMs) and costimulatory B7 antigens are also upregulated (Patard et al, 1996;Saint et al, 2001).…”
mentioning
confidence: 99%